Application of anthocyanins as natural dye extracted from Brassica oleracea L. var. capitata f. rubra: dyeing studies of wool and silk fibres . Issue 2 (17th January 2018) - Haddar, Wafa; Ben Ticha, Manel; Meksi, Nizar; Guesmi, Ahlem
Abstract: Brassica oleracea L. var . capitata f . rubra (Red Cabbage) dye is composed mainly of natural pigment called anthocyanins used as a natural colourant. Wool and silk fibres were dyed with the aqueous extract obtained from red cabbage. The dyeing process was investigated and the combined effects of dyeing conditions on the colour yield parameter ( K / S ) were studied. Resulted fastness to wash, rubbing and light of the dyed fabrics were evaluated. Chemical Oxygen Demand (COD) and Biological Oxygen Demand (BOD5) of the residual effluent were measured. Best dyeing conditions were found to be: 50 g/100 mL, pH 2, 60 min and 100 °C, respectively, for the red cabbage weight, pH, dyeing duration and temperature. Good fastnesses properties were found in both cases: for wool and silk fabrics. It was found also that the calculated biodegradability ratio (COD/BOD5 ) of the residual bath of dyeing wool and silk with red cabbage extract are lower than 1.5 which means that these baths are biodegradable. Abstract :